(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
A series of homo binuclear complexs of the type [M2(L/Lâ€™)(NO3)n(H2O)2], [where M=UO22+, Th4+, ZrO2+] and [(VO)2(L/Lâ€™)(SO4)(H2O)], L= 4, 17-di(o-hydroxyphenyl)-5,6,9,12,15,16-hexaaza-7,8,13,14-tetraphenyl heptadec-4, 6, 8, 12, 14, 16-hexene or Lâ€™= 10:11-benzo-4, 17-di(o-hydroxyphenyl)-5,6,9,12,15,16-hexaaza-7,8,13,14-tetraphenyl heptadec-4, 6, 8, 12, 14, 16-hexene, n=2 for UO22+, ZrO2+Â n=6 for Th4+, have been synthesized in template method from ethylenediamine/orthophenylene diamine, benzil monohydrazone and salicyldehyde and characterized on the basis of elemental analysis, thermal analysis, molar conductivity, magnetic moment, electronic, infrared, 1H-NMR studies.Â The results indicate that the VO(IV) ion is penta co-ordinated yielding paramagnetic complexes; UO2(VI), ZrO(IV) ions are hexa co-ordinated where as Th(IV) ion is octa co-ordinated yielding diamagnetic complexes of above composition.